The Relationship between Learning Concentration and Learning Outcomes of Students at LKP Hazika Education Center - Laras Sati; Vevi Sunarti (Universitas Negeri Padang, 2021)
This research is motivated by the low learning outcomes of students at LKP Hazika Education Center Padang City, this is thought to be due to the low concentration of students' learning during learning. This study aims to: 1) describe the concentration of students' learning; 2) describe student learning outcomes; and 3) see the relationship between learning concentration and student learning outcomes at LKP Hazika Education Center Padang City. This type of research is quantitative descriptive correlational technique. The research population of all English participants at LKP Hazika Education Center Padang City was 30 participants and a sample of 21 people were taken using cluster random sampling technique. Data collection techniques in the form of a questionnaire with a data collection tool in the form of a questionnaire. The data analysis technique uses the percentage formula and rank order correlation. The results showed that: (1) students' learning concentration was low, (2) students' learning outcomes were low, (3) there was a less significant relationship between learning concentration and student learning outcomes at LKP Hazika Education Center Padang City. Thus the concentration of learning affects student learning outcomes but not too significantly.